1995
DOI: 10.1108/13552549510086835
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis of stereolithography processes using the finite element method

Abstract: Stereolithography (SLA) is one of the most important techniques used in rapid prototyping processes. It has a great industrial interest because it allows for dramatic time savings with respect to traditional manufacturing processes. One of the main sources of error in the final dimensions of the prototype is the curl distortion effect owing to the shrinkage of the resin during the SLA process. Presents a study of the influence of different constructive and numerical parameters in the curl distortion, an analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 1 publication
0
30
0
Order By: Relevance
“…Besides, a basic solidification model in which the mechanical properties are inputs has also been discussed, proving that the shrinkage is nonlinear and a function of the absorption of laser energy and elapsed time. Bugeda et al [7] developed a finite element program for simulating the structural behavior of SLA resins by using a linear elastic model with constant Young's modulus and Poisson ratio. However, it conflicts with the reality of photopolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, a basic solidification model in which the mechanical properties are inputs has also been discussed, proving that the shrinkage is nonlinear and a function of the absorption of laser energy and elapsed time. Bugeda et al [7] developed a finite element program for simulating the structural behavior of SLA resins by using a linear elastic model with constant Young's modulus and Poisson ratio. However, it conflicts with the reality of photopolymerization.…”
Section: Introductionmentioning
confidence: 99%
“…Wiedemann et al [6] showed how the interaction between reexposed solidified resin and curing resin can influence part distortion. To simulate the deformation of a built part, Bugeda et al [7] applied the finite element method to analyse the distortion that is caused by the shrinkage effect. They used a linear elastic model with a constant Young modulus and Poisson ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In 1995, two three-dimensional finite element method (FEM) simulation computer programs [4,6] were developed. Both of them were based on the same mathematical model.…”
Section: Introductionmentioning
confidence: 99%